Process Engineering Renewal 3 - Schaer, Éric; André, J.-C. (Jean-Claude) (Wiley-ISTE, 2020)
Process engineering emerged at the beginning of the 20th Century and has become an essential scientific discipline for the matter and energy processing industries. Its success is incontrovertible, with the exponential increase in techniques and innovations. Rapid advances in new technologies such as artificial intelligence, as well as current societal needs - sustainable development, climate change, renewable energy, the environment - are developments that must be taken into account in industrial renewal. Process Engineering Renewal 3 presents a prospective analysis that demonstrates the significant disruptions linked to sustainable development, global warming, etc. These constraints may trigger changes in the social regulation system, which in turn applies pressure on actors of process engineering to evolve and adapt to these developments.